Determinants of consumer intention to accept Musharakah Mutanaqisah home financing: Empirical evidence from Malaysia and Pakistan / Imran Mehboob Shaikh - Imran Mehboob , Shaikh (2019)
This research has been carried out to determine the determinants that predict the consumer's intention to accept a specific Islamic mortgage product. Previously, some models for consumer intention were developed and proposed to enrich understanding of the issue. The theoretical framework of the current study was drawn upon the decomposed theory of planned behaviour because of its predictive power and robustness to base a model when comparing it with the theory of planned behaviour, theory of reasoned action and innovation diffusion theory. This study added the pricing variable to the proposed model and incorporates country as a moderator variable, which provides a better explanation for consumersï¿½ intention to accept mush?rakah mutan?qisah (diminishing partnership) home financing. Respondents for the current study were faculty members of three universities in Malaysia, namely, University of Malaya, University Putra Malaysia and University Kebangsaan Malaysia and three universities in the context of Pakistan, namely, University of Sindh, Bahria University and Mehran University of Engineering and Technology. Consequently, the research framework was tested using data obtained from both surveys of 610 academic staff of six universities. Data obtained from respondents were analysed using descriptive analysis, t-test, exploratory and confirmatory factor analysis with two statistical analysis software application: SPSS and AMOS. After the measurement model has achieved acceptable results and proved to have goodness-of-fit, the subsequent phase was to test the full structural model and the postulated research hypotheses as proposed in the model. A total of twenty-three hypotheses were proposed in this study based on an extensive review of the literature, out of which, twenty were supported, and three hypotheses were rejected using the t-test group difference testing. The findings of this research revealed that behavioural intention appeared to have been directly and indirectly influenced by all constructs. All the main beliefs, namely, attitude, subjective norm, perceived behaviour control, which are predicted by compatibility, relative advantage, peers and self-efficacy were significantly affecting consumersï¿½ intention to accept mush?rakah mutan?qisah home financing. The effect of pricing variable on intention was significant as well. Further, it was revealed that attitude mediated the relationship between subjective norms and intention to accept mush?rakah mutan?qisah home financing; the relationship between compatibility and consumerï¿½s intention; the relationship between relative advantage and intention. The country was a significant moderator. On the whole, the findings of the study reveal that the proposed framework elucidates a better understanding of the determinants that affect consumersï¿½ intention to accept mush?rakah mutan?qisah home financing. Around, 75% of the total variance was explained for behavioural intention. As anticipated, decomposing the main beliefs would provide more specific factors that influence the behavioural intention. The findings of this empirical research would have implications for policymakers and managers of the Islamic banking industry in order to devise a proper strategy to attract more consumersï¿½ for mush?rakah mutan?qisah home financing product.